IMPACT OF CREATING MENTAL HEALTH HELPLINE AT A TERTIARY CARE PSYCHIATRIC SET-UP IN PAKISTAN DURING THE COVID -19 PANDEMIC - Afzal, Sara; Tamizuddin Nizami, Asad; Shabbir, Fakiha; Najeeb, Bahjat; Fatima, Anum; Tahir, Zona (Journal of Pakistan Psychiatric Society, 2024)
ObjectivesThe objectives of this study were to analyze the calls received at a 24-hour helpline service set up at the Institute of Psychiatry during the first wave of the COVID-19 pandemic for the demographics of the service users, the reasons for calling the helpline phone, and the guidance provided.DesignDescriptive retrospective clinical auditPlace and Duration of StudyThe Institute of Psychiatry, from June 2020 and February 2021Patients and MethodsThe entries made detailing the call records by psychiatry residents managing the helpline were analyzed. Data was extracted regarding age, area of residence, and reasons for calling by the service users of the helpline, as well as the advice given by the resident on call. The statistical analysis was performed using SPSS version 26, and findings were evaluated in terms of age, geographical distribution, reasons for seeking assistance, and the type of guidance provided thereof.ResultsOf the 102 calls analyzed, most of the callers were between 30 to 39 years of age (33.3%), and hailed from Rawalpindi (78.4%), followed by Kashmir (5.9%), Chakwal (4.9%) and Murree (3.9%). The most frequently stated reasons for calling were to ask about availability of out-patient services (36.3%), to have medication revised (23.5%), and to enquire about the side effects of medication (11.8%). Other reasons included recurrence of symptoms or lack of improvement in patients already taking treatment (15.7%) and to seek help regarding new psychiatric symptoms (12.7%). The responses given to the callers were invitation to come to the hospital (44.1%), provision of relevant information about the particular questions asked (for example, relating to hospital timings) (36.3%), adjustment of medications (11.8%), and prescribing medication with advice of physical follow-up (7.8%).ConclusionDespite psychiatric out-patient department being temporarily closed down during the initial waves of the COVID 19 pandemic, efforts were made to continue service provision through innovative means, like the 24-hour helpline service. There is a need to further incorporate the use of technology in the delivery of psychiatric services.